2020
DOI: 10.1111/cea.13601
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world experience with mepolizumab: Does it deliver what it has promised?

Abstract: Background: Randomized control trials performed in selected populations of severe eosinophilic asthmatics have shown that mepolizumab, an anti-IL5 therapy, was able to reduce exacerbations and OCS maintenance dose and in some studies, to improve asthma control and lung function.Objective: The aim of this study was to confirm the results of the RCTs in real-life in a population of 116 severe eosinophilic asthmatics treated with mepolizumab and who were followed up at the asthma clinic every month for at least 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
36
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 25 publications
(35 reference statements)
11
36
0
3
Order By: Relevance
“…Of the 1757 potentially relevant records identified in the initial search, 59 real-world studies were deemed eligible for a qualitative analysis. Six studies were carried out on benralizumab [34][35][36][37][38][39], 1 on dupilumab [40], 18 on mepolizumab [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58], 27 on omalizumab [18,, and 3 on reslizumab [85][86][87]. Four studies investigated different mAbs in the same report [88][89][90][91].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 1757 potentially relevant records identified in the initial search, 59 real-world studies were deemed eligible for a qualitative analysis. Six studies were carried out on benralizumab [34][35][36][37][38][39], 1 on dupilumab [40], 18 on mepolizumab [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58], 27 on omalizumab [18,, and 3 on reslizumab [85][86][87]. Four studies investigated different mAbs in the same report [88][89][90][91].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In a large and long-term study [46] carried out in severe eosinophilic asthmatic patients, the treatment with mepolizumab for 2.5 years elucidated a significant and maintained reduction by 50% in the dose of oral corticosteroids as compared to baseline. This data was confirmed by another large and long-term study [47] in which, after 1 year and 2 years of treatment with mepolizumab, the use of OCS dropped from 92.8% at baseline to 41.1% and 34.7%, respectively.…”
Section: Mepolizumabmentioning
confidence: 99%
“…[231][232][233][234][235][236][237] Real-world studies have similarly shown that these drugs were safe and efficacious, with response rates around 70%, and improvements in clinical asthma outcomes (exacerbations, OCS dependence, asthma control, quality of life, lung function), as early as 4-weeks into therapy. 26,[238][239][240][241][242][243][244][245][246][247][248] Their clinical efficacy was also observed in real-world patients who had failed Omalizumab therapy. 225,226,249,250 Real-world characterisation of patients receiving anti-IL-5/IL-5R drugs has identified a group who are older in age, have adult-onset asthma, predominantly male and have a high prevalence of nasal polyposis.…”
Section: Omalizumabmentioning
confidence: 83%
“…In a real-world study including 116 patients from Belgium, the best predictor of a reduction in exacerbations with mepolizumab was a higher baseline total serum IgE level. This implies IgE-mediated mechanisms in propagating IL-5 [29]. In accordance, benralizumab might also interfere with IgE-dependent immune responses, since in a real-world study from Italy all 22 patients recruited who decreased significantly the rate of exacerbations were allergic [35].…”
Section: Differential Response To Anti-il5s: Observations and Possible Explanationsmentioning
confidence: 90%
“…Patients significantly improved their asthma control, as assessed by ACT and ACQ scores as well as quality of life (AQLQ score) at 6 months and this was also maintained throughout the follow-up. Eventually, a progressive improvement in FEV 1 that reached significance after 18 months was observed, and this was more pronounced in patients with a higher baseline sputum eosinophil percentage [29].…”
Section: Mepolizumabmentioning
confidence: 90%